2(g-2)-4=2(2g-3)

Simple and best practice solution for 2(g-2)-4=2(2g-3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(g-2)-4=2(2g-3) equation:


Simplifying
2(g + -2) + -4 = 2(2g + -3)

Reorder the terms:
2(-2 + g) + -4 = 2(2g + -3)
(-2 * 2 + g * 2) + -4 = 2(2g + -3)
(-4 + 2g) + -4 = 2(2g + -3)

Reorder the terms:
-4 + -4 + 2g = 2(2g + -3)

Combine like terms: -4 + -4 = -8
-8 + 2g = 2(2g + -3)

Reorder the terms:
-8 + 2g = 2(-3 + 2g)
-8 + 2g = (-3 * 2 + 2g * 2)
-8 + 2g = (-6 + 4g)

Solving
-8 + 2g = -6 + 4g

Solving for variable 'g'.

Move all terms containing g to the left, all other terms to the right.

Add '-4g' to each side of the equation.
-8 + 2g + -4g = -6 + 4g + -4g

Combine like terms: 2g + -4g = -2g
-8 + -2g = -6 + 4g + -4g

Combine like terms: 4g + -4g = 0
-8 + -2g = -6 + 0
-8 + -2g = -6

Add '8' to each side of the equation.
-8 + 8 + -2g = -6 + 8

Combine like terms: -8 + 8 = 0
0 + -2g = -6 + 8
-2g = -6 + 8

Combine like terms: -6 + 8 = 2
-2g = 2

Divide each side by '-2'.
g = -1

Simplifying
g = -1

See similar equations:

| 3.50x+36=5x | | -6=-2/x | | a=-10.6-1.5a | | 2x-16=2x-8 | | 10.3x+1=2x+4 | | 2lnx-ln(2x-7)=ln(9x)-ln(x-2) | | -14k^2-280=0 | | 3z-1z+2z-30=70 | | x+10=-100 | | 9x+10=8+8x | | 5/(x-4)=0 | | -2(2x-5)=2(X-7) | | 3y-1z+2z-30=70 | | -10x^2+22x+12=0 | | 13=p-(-15) | | 5x(4-x)=9-(x-6) | | -10y-5y=120 | | 2cos(0.5)-1=0 | | 7=b+2 | | r^2-10x-50=0 | | -6x-1x=56 | | -4/4=x | | 96x-9/2x^2 | | 2x^2-7x-16=0 | | Z-br=pforb | | 7+5k=-13+2k-2k | | 3x+4=5x+10-2x | | 3.6−2.5(4.8÷1/2)= | | 2*1.2-y=2 | | 5x+5=-6x+2 | | 3.6−2.5(4.8÷1/2) | | 15x-10x=5x |

Equations solver categories